Afghan and Arab Refugee International Medical Graduate Brain Waste: A Scoping Review - Ahmad Fahim Pirzada; Zaina Chaban; Andrea Michelle Guggenbickler; Seyedeh Ala Mokhtabad Amrei; Arliette Ariel Sulikhanyan; Laila Afzal; Rashim Hakim; Patrick Marius Koga (Social Sciences)
The forced migration of tens of thousands of refugee doctors exacerbates a phenomenon referred to as “brain waste”. Based on the Arksey and O’Malley model, this scoping review conducted in SCOPUS, ProQuest, CINAHL, and ERIC via EBSCO examines three decades of peer-reviewed literature (1990–2022) on resettled Afghan and Arab refugee International Medical Graduates (rIMGs) attempting, most often unsuccessfully, relicensing/professional reentry in the USA, Canada, the EU, Australia, and New Zealand. The search identified 760 unique citations, of which only 16 met the inclusion/exclusion criteria. Included publications explored (1) systemic and personal barriers to rIMG professional reentry and (2) existing supporting reentry programs and policy recommendations. The findings point to inconsistencies in evaluating medical education credentials and to racial profiling, inequities, and discrimination in residency interviews. The support provided by some programs was perceived as inadequate, confusing, biased, and gendered. The rIMG personal barriers identified included refugees’ unique limitations and life adversities. The review grasps a collection of isolated support programs with widely varying learning performance, unclear buy-in from residency program directors, and weak policy impacts. This analysis highlights the need for legislated and standardized rIMG reentry support programs to reduce physician shortages, health disparities, and, ultimately, IMG brain waste.